Otimalisasi SDM dan Digital Marketing Untuk Pengembangan Lembaga Seni Budaya Pajaga Ada’ Di Era Digital - SYAMSUL BAKHTIAR ASS; Yuni Kartini; Abdillah SAS (Universitas Muhammadiyah Sidenreng Rappang, 2025)
Art is one of the indicators in preserving and maintaining national identity. This forms a nation’s character, as it possesses a wide diversity of arts and cultures framed within the principle of Bhinneka Tunggal Ika (Unity in Diversity). LSB Pajaga Ada’ is one of the institutions engaged in the fields of art and culture in Maros Regency. In its development, it faces obstacles and challenges in the era of digitalization. Therefore, LSB Pajaga Ada’ requires solutions to address these issues by becoming a partner in the Community Partnership Empowerment Program (PKM). The purpose of this community service activity is to optimize human resources and digital marketing in the development of LSB Pajaga Ada’ in the digital era. The research method employs five stages: (1) socialization; (2) training; (3) technology implementation; (4) mentoring and evaluation; and (5) program sustainability. The results indicate an improvement in human resource capabilities and digital marketing management through the use of Meta Verified Instagram, Canva Pro accounts, and a website, as well as the development of artistic works. In conclusion, the training participants experienced increased skills and mastery in human resource management, digital marketing, and the utilization of Canva and websites.